Calibration and Application of Branched GDGTs to Tibetan Lake Sediments: The Influence of Temperature on the Fall of the Guge Kingdom in Western Tibet, China. Issue 5 (30th April 2022) - Liang, Jie; Guo, Yanlong; Richter, Nora; Xie, Haichao; Vachula, Richard S.; Lupien, Rachel L.; Zhao, Boyang; Wang, Mingda; Yao, Yuan; Hou, Juzhi; Liu, Jianbao; Russell, James M.
Abstract: Branched glycerol dialkyl glycerol tetraethers (brGDGTs) from lacustrine sediments have been widely used to reconstruct mean annual air temperature (MAAT). Although many proxy calibrations relating brGDGT characteristics have been put forth, these calibrations may produce warm biases when applied to lakes in cold regions. We present an expanded Chinese lake surface sediment brGDGT‐MAAT calibration with 29 new surface samples from cold regions along with 39 previously published from Chinese lakes. We deployed sediment traps in a meromictic lake, Dagze Co, and compared results with previously published data from a dimictic lake, Lake 578 in Greenland, to determine potential seasonal and depth‐dependence of brGDGTs. In the meromictic lake, brGDGTs are primarily produced in the lake bottom water, whereas in the dimictic lake, the brGDGTs are produced throughout the water column and mainly reflect the annual bottom water temperature or mixing season water column temperature. We applied our refined calibration to a sediment core from Western Tibet to examine how fluctuations in temperature influenced the Guge Kingdom over the last 2, 000 years. Our record reveals relatively warm temperatures during the Medieval Climate Anomaly, cooling of 2°C to −2°C during the Little Ice Age, warming into the eighteenth century, and stabilization after 1800 CE. The temperature variations coincided with a transition of dynasties in Western Tibet. Temperature sensitivity tests on barley distribution, the principal cultivated cereal in Tibet, suggest that a decline in temperature led to a decreased crop yield that may have factored into the disappearance of the Guge Kingdom. Plain Language Summary: Paleoclimate reconstructions from lake sediments can provide a wealth of information on past climate changes. The accuracy of these reconstructions depends on a modern "translation" between proxies and climate variables. Lacustrine branched glycerol dialkyl glycerol tetraethers (brGDGTs) are viewed as a promising tool for reconstructing air temperatures. However, there is not a one‐to‐one correlation between air temperatures and lacustrine brGDGT‐based temperatures; therefore, we have to conduct calibration studies to understand how they are related. In this study, we compared sediment traps in a meromictic and dimictic lake to determine niche partitioning of brGDGTs. Comparisons between core‐top reconstructed and observed water column temperatures show that in meromictic lakes, brGDGTs are primarily produced in the lake bottom water, whereas in the dimictic lakes, they are produced throughout the entire water column and reflect annual bottom water temperatures or water column temperatures during the mixing season. We then establish a new calibration and apply it to a lake sediment record, which indicates that temperatures cooled during 1630 CE. This time period coincides with the disappearance of the Guge Kingdom. Using ecological niche modeling, we confirm that cooling led to a decline in barley, which has likely contributed to the collapse of the Kingdom. Key Points: Different lake mixing types profoundly impact brGDGT‐reconstructed temperatures Air temperatures in Western Tibet were 2–3°C cooler than present during the LIA Temperature variability influenced crop yield. A decreased crop yield likely contributed to the collapse of the Guge Kingdom